Neoadjuvant therapy in pancreatic neuroendocrine neoplasms: A systematic review and meta-analysis - Yongzheng Li; Zhiyao Fan; Feifei Zhang; Jian Yang; Ming Shi; Shujie Liu; Yufan Meng; Hanxiang Zhan (Frontiers in Oncology, 2022)
Background and ObjectivesNeoadjuvant therapy plays an increasingly important role in pancreatic neuroendocrine neoplasms (pNENs), but the systematic evaluation of its efficacy is still lacking. The purpose of this study is to explore the role of neoadjuvant therapy in pNENs.MethodsWe systematically reviewed the literatures published online until October 1, 2021. Meta-analysis was conducted to generate proportion with 95% confidence intervals (95% CI) for tumor response, resection rate, R0 resection rate and survival time.ResultsNine studies with 468 patients were involved in the systematic review. None of these patients met complete response (CR). Furthermore, 43.6% (95% CI [18.1, 69.0]) patients were expected to achieve partial response (PR), 51.3% (95% CI [27.9, 78.3]) to stable disease (SD), and 4.3% (95% CI [0.7, 7.9]) to progressive disease (PD). The estimate resection rate and R0 resection rate after neoadjuvant therapy were 68.2% (95% CI [44.5, 91.9]) and 60.2% (95% CI [53.5, 66.9]), respectively. There was no significant difference in resection rate between different chemotherapy regimens (41.67% vs 33.93%, P=0.453), as well as R0 resection rate (62.50% vs 68.30%, P=0.605). In terms of objective response rate (ORR), there was no significant difference between CAPTEM and FAS (41.67% vs 33.93%, P=0.453), while PRRT showed a higher ORR compared with chemotherapy, although there was also no statistical difference (49.06% vs 36.96%, P=0.154).ConclusionNeoadjuvant therapies could reduce the tumor size and stage of some borderline resectable or unresectable pNENs, and give some patients the chance of radical resection. However, according to the current data, the best treatment regimen for pNENs neoadjuvant therapy is still unknown.